Neuroticism and Its Associated Brain Activation in Women With PTSD. Issue 1 (January 2020) - Brown, Nicholas; Wojtalik, Jessica A.; Turkel, Melissa; Vuper, Tessa; Strasshofer, David; Sheline, Yvette I.; Bruce, Steven E.
Previous research suggests a diathesis-stress model of posttraumatic stress disorder (PTSD), wherein individuals with high levels of neuroticism who are exposed to traumatic events subsequently develop PTSD. Although studies have established relationships between neuroticism and neurological functioning in various brain regions for healthy and depressed individuals, the specific neural correlates of neuroticism for individuals with PTSD are yet unknown. This relationship is particularly relevant for women, given that their increased risk for PTSD is partially accounted for by their higher baseline levels of neuroticism. The current study examined previously established neural correlates of neuroticism in 61 women (48 women with interpersonal violence [IPV]/PTSD and 13 healthy controls). A specific region of interest map, including the amygdala, hippocampus, parahippocampus, anterior cingulate cortex (ACC), and dorsal medial prefrontal cortex (dmPFC), was examined while participants completed an emotional conflict task. Results showed that the PTSD group had significantly higher neuroticism scores than the healthy control group ( t = 6.90, p < .001). Higher neuroticism scores were associated with increased neural activity in the right dmPFC when participants were instructed to directly attend to faces with negative emotional valences. Significant trends between higher neuroticism scores and greater right amygdala and right ACC activation also emerged for this condition. Finally, neuroticism was found to be associated with right amygdala and right parahippocampal activity when participants were instructed to ignore faces with negative emotional valences. The results of this study lend further evidence to the proposed diathesis-stress model of neuroticism and PTSD. Moreover, findings suggest a significant association between neuroticism and neural activity in brain regions associated with fear and emotion regulation for women with IPV and subsequent PTSD.